4(x+14)-3(-x+7)=28

Simple and best practice solution for 4(x+14)-3(-x+7)=28 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(x+14)-3(-x+7)=28 equation:



4(x+14)-3(-x+7)=28
We move all terms to the left:
4(x+14)-3(-x+7)-(28)=0
We add all the numbers together, and all the variables
4(x+14)-3(-1x+7)-28=0
We multiply parentheses
4x+3x+56-21-28=0
We add all the numbers together, and all the variables
7x+7=0
We move all terms containing x to the left, all other terms to the right
7x=-7
x=-7/7
x=-1

See similar equations:

| 3(2x+1)=-3(2x-2)-4x | | 7x=2x+37 | | 5(x-1)=5(x-3) | | 180(n-2)=29700 | | 180(n-2)=3420 | | X28=14x14 | | 26n=-4 | | 5x-3x+1=2x+5 | | 3f+2=2(f+10.5) | | (3-k)2+(3+k)4=60 | | -55-(3u)=8 | | 2.4k-0.7=18.02 | | -10-5h=14 | | 64x-10=22 | | 2.4k-0.7=1802 | | 16/y+8+2/y=10y-8/y^2-64 | | 28=17/23x-23 | | 5m+64=49-2m | | -0.7×2.4k=18.02 | | (-5)=x-2x+3 | | (-5)=x-2x+ | | 15/y+5+3/y=13y-5/y^2-25 | | 7x(x+3)=(x)(7x-3)+36 | | (5x+9)=(6x-15) | | +-9=-5/6x | | 16^(1-x)=12 | | -4y-(9)=15 | | (1+X)/(-10+x)=0 | | (5x+9)°=(6x-15)° | | 2y-5=12y+85 | | 0.2(10x+11)=3(0.2x+5) | | 4p+4=(2p+36) |

Equations solver categories